2020
DOI: 10.1093/conphys/coaa017
|View full text |Cite
|
Sign up to set email alerts
|

Conservation seed physiology of the ciénega endemic, Eryngium sparganophyllum (Apiaceae)

Abstract: Knowledge of seed dormancy and optimal propagation techniques is crucial for successful ex situ restoration and reintroduction projects, and determining the seed storage behaviour of a species is critical for the long-term conservation of seeds, further supporting future ex situ efforts. Eryngium sparganophyllum (Apiaceae) is a globally critically endangered plant species endemic to ciénega wetlands of southwest North America. To support in situ and ex situ conservation efforts of E. sparganophyllum, we asked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…This supports the hypothesis that E. maritimum seeds are physiological (PD) or morphophysiological dormant (MPD), and so they need a trigger, in this case, a cold stratification period to begin germination. Considering that MPD was reported by Necajeva and Ievinsh (2013), it can be suggested that embryos are incompletely developed as morphophysiological dormant seeds at the end of the fruiting period (Wolkis et al 2020), and so they have to develop during autumn and winter, while they need some high temperatures at spring to begin the germination process (Vandelook et al 2012). Moreover, seeds from the Atlantic population germinated better at 15°C, which could be linked with the same hypothesis, and so suggests that the species has been able to adapt its ecological germination requirements to the specific…”
Section: Optimal Incubation Temperaturementioning
confidence: 71%
See 1 more Smart Citation
“…This supports the hypothesis that E. maritimum seeds are physiological (PD) or morphophysiological dormant (MPD), and so they need a trigger, in this case, a cold stratification period to begin germination. Considering that MPD was reported by Necajeva and Ievinsh (2013), it can be suggested that embryos are incompletely developed as morphophysiological dormant seeds at the end of the fruiting period (Wolkis et al 2020), and so they have to develop during autumn and winter, while they need some high temperatures at spring to begin the germination process (Vandelook et al 2012). Moreover, seeds from the Atlantic population germinated better at 15°C, which could be linked with the same hypothesis, and so suggests that the species has been able to adapt its ecological germination requirements to the specific…”
Section: Optimal Incubation Temperaturementioning
confidence: 71%
“…Many species in the Apiaceae are reported to exhibit morphological dormancy (MD) or morphophysiological dormancy (MPD) (Finch-Savage and Leubner-Metzger 2006;Baskin and Baskin 2014), including the Genus Eryngium (Wolkis et al 2020). In MPD, the seed coat is water permeable, embryos are undeveloped and also have a physiological inhibiting mechanism that requires an ecological signal to elicit germination (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…To elucidate the effects of gibberellic acid (GA 3 ) on germination, a one-way factorial layout with solutions of 0 (control), 250, 500, 750 and 1000 ppm GA 3 was used. The full experimental design involved two factors but we followed the original analysis described by Wolkis et al (2020). For each solution, there were three replicates of 16 seeds that were sown in 90-mm Petri dishes on silica sand moistened with sterilized distilled water and placed inside a resalable zip-top plastic bag to preserve moisture.…”
Section: Methodsmentioning
confidence: 99%
“…Example 1: a one-way factorial design Wolkis et al (2020) investigated conservation seed physiology of the ciénega (freshwater emergent wetlands) endemic, Eryngium sparganophyllum (Apiaceae), including storage behaviour and dormancy. In this example, we re-examine the authors' experiment testing germination response to varying concentrations of gibberellic acid.…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation